2015
DOI: 10.1063/1.4926819
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent evolution of plasma discharge and electromagnetic fields in a microwave pulse compressor

Abstract: Nanosecond-scale evolution of plasma and RF electromagnetic fields during the release of energy from a microwave pulse compressor with a plasma interference switch was investigated numerically using the code MAGIC. The plasma was simulated in the scope of the gas conductivity model in MAGIC. The compressor embodied an S-band cavity and H-plane waveguide tee with a shorted side arm filled with pressurized gas. In a simplified approach, the gas discharge was initiated by setting an external ionization rate in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…One can see that, for the focused beam, the peak power is more than two times higher, the rise time of the pulse is about two times shorter, the "flattop" is longer, and the delay with respect to the triggering event is dramatically shorter than for the unfocused beam. There is a good qualitative agreement between the output pulse waveforms and delays and the results of the simulations, 8 in which the seed electrons set in the filamentlike volume differed in density by six orders of magnitude. Thus, the focused beam evidently creates a much higher density of seed electrons, so that plasma filaments having sufficient length and density for efficient microwave reflection are formed in a time much shorter than the output pulse duration.…”
supporting
confidence: 61%
See 4 more Smart Citations
“…One can see that, for the focused beam, the peak power is more than two times higher, the rise time of the pulse is about two times shorter, the "flattop" is longer, and the delay with respect to the triggering event is dramatically shorter than for the unfocused beam. There is a good qualitative agreement between the output pulse waveforms and delays and the results of the simulations, 8 in which the seed electrons set in the filamentlike volume differed in density by six orders of magnitude. Thus, the focused beam evidently creates a much higher density of seed electrons, so that plasma filaments having sufficient length and density for efficient microwave reflection are formed in a time much shorter than the output pulse duration.…”
supporting
confidence: 61%
“…The discharge originates from the center of the waveguide cross-section, and the plasma in the switch appears as a filament expanding along the RF electric field. 6 This process was simulated numerically, 8 and it was shown that a low extraction efficiency is inevitable when the time of the filament formation with sufficiently high plasma density is longer than the round-trip time of the traveling wave along the cavity (output pulse length). In this case, the extraction of the output pulse limits its own power, since the RF electric field in the switch decreases to the level at which it no longer supports the electron avalanche.…”
mentioning
confidence: 99%
See 3 more Smart Citations